Normative noninvasive bladder function measurements in healthy women: A systematic review and meta‐analysis. Issue 2 (9th January 2020) - Wyman, Jean F.; Zhou, Jincheng; Yvette LaCoursiere, D.; Markland, Alayne D.; Mueller, Elizabeth R.; Simon, Laura; Stapleton, Ann; Stoll, Carolyn R. T.; Chu, Haitao; Sutcliffe, Siobhan
Abstract: Aim: To conduct an evidence synthesis of normative reference values for bladder function parameters in women. Methods: We conducted a systematic review and meta‐analysis of studies reporting bladder function parameters obtained from noninvasive tests in healthy women. Seven databases were searched for relevant studies from inception through December 2018, with manual searching of reference lists. We included English language articles that provided quantitative data on urination frequency, voided and postvoid residual volumes, and uroflowmetry results in women without lower urinary tract symptoms. Study selection, data extraction, and quality assessment were undertaken by at least two independent reviewers. Random‐effects meta‐analytic models were used to derive study‐level pooled mean estimates and 95% confidence intervals. Results: A total of 24 studies (N = 3090 women, age range, 18‐91 years) met eligibility criteria. Pooled mean estimates of bladder function parameters were: 6.6 daytime voids (95% confidence interval (95% CI), 6.2, 7.0), 0.4 nighttime voids (95% CI, 0.0, 0.8), 1577 mL for 24‐hour voided volume (95% CI 1428, 1725); 12 mL for postvoid residual volume (95% CI, 4, 20); and 28 mL/sec for maximum flow rate (95% CI, 27, 30). Between‐study heterogeneity was high for all outcomes ( I 2 = 61.1‐99.6%), but insufficient data were available to explore reasons for this high heterogeneity (eg, differences by age). Conclusion: Although summary mean estimates of bladder function parameters were calculated, the wide heterogeneity across studies precludes generalization of these estimates to all healthy women. Further research is needed to determine normative reference values within specific groups, such as those defined by age.